Versatility of Compaction Grouting to Stabilize and Lift Large Structures - Joe Harris (Deep Foundations Institute, 2023)
Large structures, such as a multistory office building or a large storage tank, are constructed the most economical way possible, which may involve a shallow foundation system placed on native soil or compacted fill material. Over the life of the structure, the foundation system may not perform as originally anticipated, leading to differential settlement. Minor differ- ential settlement is expected; however, settlement that exceeds allotted tolerance can render the structure inoperable. Compaction grouting is a well-known and accepted ground improvement technique that can be used to not only stabilize but relevel multistory buildings and large dia- meter storage tanks. Two projects, each with differing types of structures, were successfully remediated utilizing com- paction grouting as the primary method to remedy settlement.